Water transport into PEFC gas diffusion layer: experimental characterization of diffusion and permeation. (17th June 2013) - Bresciani, F.; Casalegno, A.; Varisco, G.; Marchesi, R.
SUMMARY Optimization of water management in low‐temperature polymer electrolyte fuel cells is an important subject for the achievement of high performance and sufficient lifetime. Indeed, good hydration of the electrolyte membrane is essential for high proton conductivity; on the contrary, water in excess may lead to electrode flooding especially at the cathode where water is produced. Water transport through the gas diffusion layer, from cathode electrode to distributor flow field, occurs via diffusion and permeation mechanisms: these phenomena are not fully explained, and the onset of the second one, usually named as breakthrough, can play an important role on cathode water balance. This work aims to investigate diffusive and permeative water transport through the diffusion layer under fuel cell representative operating conditions. The effect of microporous layer on diffusion layer effective diffusivity is estimated, and the contribution of the Knudsen diffusion is evaluated. The microporous layer presence determines a strong increase in breakthrough pressure; moreover, cracks are responsible for breakthrough. At high water saturation in the diffusion layer, a considerable hysteresis effect on breakthrough pressure is present. Copyright © 2013 John Wiley & Sons, Ltd.